WHAT FACTORS AFFECT THE FRAUD DETECTION? THE ROLE OF RED FLAGS AND AUDITOR EXPERIENCE - Fakhmi Zakaria; Suhita Whini Setyahuni (Jurnal Akuntansi dan Perpajakan, 2023)
This study intends to investigate what factors that affects fraud detection. We focus on the effect of red flags and auditor experience as the determinant factors. We also investigate the role of moderating of auditors experience on the relationship between red flags and fraud detection. We use 57 sample of auditors in the Regional Inspectorate of Central Java Province during 2022 . We employ Partial Least Square (PLS)Â  as an analysis tool to test the hypotheses. Our findings shows that there are a positive impact od red flags and auditor experience on the fraud detection. However, auditor experience does not play a moderating role on the relationship between red flags and fraud detection. Our findings contribute to the development of fraud detection literature based on attribution theory. We provide empirical evidences on what factors affecting fraud detection.